Decision Support System to Determine the Right Department in Higher Education Based on the Interests and Talents of Prospective Students by Applying the AHP Method - Dewi, Nur Kumala (International Journal of Educational Research & Social Sciences, 2021)
The background of this research is how to determine the best choice in determining a major in higher education, with various existing majors, students must be able to choose the right department for themselves, with the right majors, the lectures will be maximized and the student will not experience difficulties. in entering lectures. The method used in this study is to use quantitative methods, based on literature reviews, with literature review methods, it will refer to previous research that has produced something for the wider community, with the development of previous research, this research will become the latest research. . There are several studies that use the AHP method, for example in the field of decision support systems in the field of psychology, the recruitment department of new employees, using the AHP method can determine which employee is the best for a position in a company, this method will help HRD in determining acceptable employees in a company. This research will show how an AHP method can provide the best solution in choosing a department in a college, which is carried out on prospective new students at a university.